Ink and application thereof
By using ink containing conductive polymers with crosslinking groups and organic matter of thiol groups, a dense film is prepared as a barrier layer for the charge generation layer, which solves the problem of insufficient life of the stacked light emitting device in the solution process, and achieves better charge generation and separation capabilities and device performance.
Patent Information
- Application Number
- CN202311253446.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
AI Technical Summary
In the solution process, the development of stacked light emitting devices is affected by physical and chemical damage of completed films and high-temperature annealing treatment on device performance, resulting in insufficient device life.
An ink is provided, a conductive polymer containing a crosslinking group, an organic substance containing a thiol group and a solvent that can react with a crosslinking group to prepare a dense film as a barrier layer for the charge generation layer.
The film prepared by crosslinking reaction has good density and anti-soluble ability, which can inhibit the damage of the hole functional layer to the electronic functional layer, improve charge generation and separation capabilities, and extend the device life.
Smart Images

Figure CN119708910A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of display technology, and more specifically, to an ink and its application. Background Art
[0002] Organic electroluminescent devices (OLEDs) and quantum dot light-emitting devices (QLEDs) have outstanding advantages in large-area and rich-shaped terminal display screens, but they usually have a shorter lifespan than traditional inorganic electroluminescent devices. Therefore, when designing the device, two light-emitting devices can be connected in series (stacked devices). In this way, the current density required by the device at the same brightness is reduced, thereby increasing the lifespan of the device. This is also an important direction for improving the lifespan of OLEDs.
[0003] In a stacked light-emitting device, the cathode / anode connecting multiple light-emitting units is usually replaced by a charge generation layer, which is relatively easy to achieve in an evaporation process. However, in a solution process, it is necessary to evaluate the physical and chemical damage to the completed thin film and the impact of high-temperature annealing treatment on device performance, making the development of solution-based stacked light-emitting devices more difficult. Summary of the invention
[0004] Based on this, an embodiment of the present application provides an ink and its application.
[0005] In order to solve the above technical problems, the present application embodiment provides an ink, which adopts the following technical solution:
[0006] An ink comprises: a conductive polymer containing a cross-linking group, an organic substance containing a thiol group and a solvent, wherein the thiol group is configured to be capable of cross-linking reaction with the cross-linking group.
[0007] Furthermore, the conductive polymer has the following general formula I:
[0008]
[0009] Wherein, m is selected from an integer of 5 to 100;
[0010] R is the crosslinking group, and R contains a vinyl group.
[0011] Furthermore, the vinyl group is selected from norbornene end groups and has the following general formula II:
[0012]
[0013] Here, x is an integer selected from 0 to 5.
[0014] Furthermore, the mass average molecular weight (Mw) of the conductive polymer is greater than 10000; and / or
[0015] The organic compound is selected from at least one of formulas Ⅰ, Ⅱ, Ⅲ, Ⅳ, Ⅴ, and Ⅵ:
[0016]
[0017]
[0018] Wherein, n is selected from an integer of 10 to 100;
[0019] and / or
[0020] The mass ratio of the conductive polymer to the organic matter is (1:1) to (50:1).
[0021] Furthermore, the solvent is selected from at least one of tetralin, decalin, cyclohexylbenzene, xylene, toluene, chlorobenzene, chloroform, anisole, methyl benzoate, ethyl benzoate, n-propyl benzoate, cyclohexanone, tetrahydrofuran, dioxane, and acetophenone.
[0022] In order to solve the above technical problems, the present application also provides a method for preparing a thin film, which adopts the following technical solution:
[0023] A method for preparing a thin film comprises the following steps:
[0024] Providing a preform, and placing ink on the preform to obtain a liquid film; the ink comprises a conductive polymer containing a cross-linking group, an organic substance containing a thiol group, and a solvent;
[0025] The liquid film is placed at a first temperature to react to obtain a thin film.
[0026] In order to solve the above technical problems, the embodiment of the present application further provides a charge generation layer, which adopts the following technical solution:
[0027] A charge generating layer comprises a barrier layer, wherein the barrier layer is prepared by using the ink as described above, or the barrier layer is prepared by using the preparation method as described above.
[0028] Furthermore, the charge generation layer includes a hole functional layer and an electron functional layer which are stacked, the barrier layer is arranged between the hole functional layer and the electron functional layer, and the material of the hole functional layer includes a hole injection material and an oxidant.
[0029] Furthermore, the thickness of the barrier layer is 5 to 100 nm; and / or
[0030] The thickness of the hole functional layer is 5 to 100 nm; and / or
[0031] The mass ratio of the hole injection material to the oxidant is (1:0) to (1:1); and / or
[0032] The hole injection material is selected from at least one of phosphomolybdic acid, phosphotungstic acid, ammonium molybdate, metavanadic acid, metatungstic acid, vanadyl acetate acetonate, tungsten ethoxide, molybdenum ethoxide, PEDOT:PSS, HATCN, CN6-CP, NDP-9, F4TCNQ and F6TCNQ; and / or
[0033] The oxidant includes at least one of iron (III) chloride, antimony chloride, iron benzenesulfonate, iron pentafluorobenzenesulfonate (FeTos3), iron (III) trifluoromethanesulfonate, nitrosyl hexafluorophosphate, tris (pentafluorophenyl) boric acid, and tris (4-bromophenyl) ammonium hexachloroantimonate.
[0034] Further, the material of the electronic functional layer includes metal oxide;
[0035] The metal oxide is selected from at least one of doped or undoped zinc oxide, tin oxide, titanium oxide and zirconium oxide, and the doped elements include at least one of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium and gadolinium.
[0036] Furthermore, the material of the electronic functional layer further comprises an organic material, and the organic material is selected from at least one of aliphatic amine polymers and organic electron transport materials; and / or
[0037] The thickness of the electronic functional layer is 5-100 nm.
[0038] In order to solve the above technical problems, the embodiment of the present application further provides a light emitting device, which adopts the following technical solution:
[0039] A light-emitting device comprises a first electrode, a first light-emitting unit, the charge generation layer as described above, a second light-emitting unit and a second electrode which are stacked.
[0040] Furthermore, the first electrode and the second electrode are each selected from one or more of a metal electrode, a silicon-carbon electrode, a doped or undoped metal oxide electrode and a composite electrode; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca and Mg; the material of the silicon-carbon electrode is selected from at least one of silicon, graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, At least one of IZO, MZO and AMO; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or
[0041] The first light-emitting unit and the second light-emitting unit each include a hole transport layer, a light-emitting layer and an electron transport layer which are stacked in sequence, the hole transport layer is arranged adjacent to the first electrode, and the electron transport layer is arranged adjacent to the second electrode; the material of the hole transport layer is selected from at least one of TFB, poly-TPD, PVK, BFB, and PFHB; and / or
[0042] The light-emitting layer is a quantum dot light-emitting layer or an organic light-emitting layer; the material of the quantum dot light-emitting layer includes at least one of a single structure quantum dot and a core-shell structure quantum dot, and the material of the single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound, wherein the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe , at least one of CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, S At least one of nPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInN P, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs or InAlPSb, the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; the core of the quantum dots of the core-shell structure includes any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure includes CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS, ZnS and at least one of the above-mentioned single-structure quantum dots;The material of the organic light-emitting layer includes at least one of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine-C2,N)iridium(III), 4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine-C2,N)iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials and DBP fluorescent materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives; and / or;
[0043] The material of the electron transport layer is selected from at least one of doped or undoped metal oxides and organic electron transport materials; the doped or undoped metal oxide is selected from at least one of doped or undoped zinc oxide, tin oxide, titanium oxide, and zirconium oxide, and the doped element includes at least one of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic electron transport material is selected from [6,6]-phenyl C71 butyric acid methyl ester, [6,6]-phenyl C61 butyric acid methyl ester, organic fullerene materials, 2-ethyl-1-(4-(10-(2-naphthyl)-9-anthracenyl)phenyl)-1H-benzimidazole, 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene, 3,3'-[5'-[3-(3-pyridyl)phenyl], 4,6-bis(3,5-di(3-pyridyl)phenyl)-2-methylpyrimidine, beryllium phenylidene pyridine, 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene, 3-(biphenyl-4-yl)-5-(4-tert-butylphenyl)-4-phenyl-4H-1,2,4-triazole, 1,3,5-tris[(3-pyridyl)-3-phenyl]benzene, tris-(8-hydroxyquinoline)aluminum, 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline, 4,7-diphenyl-1,10- At least one of phenanthroline, poly[(9,9-bis(3'-((N,N-dimethyl)-N-ethylammonium)-propyl)-2,7-fluorene)-2,7-(9,9-dioctylfluorene)] dibromide, poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)-2,7-fluorene)-2,7-(9,9-dioctylfluorene)], and 2,7-bis(diphenylphosphinyl)-9,9'-spirobi[fluorene].
[0044] In order to solve the above technical problems, the embodiment of the present application further provides a display device, which adopts the following technical solution:
[0045] A display device includes the charge generation layer as described above, or includes the light emitting device as described above.
[0046] Compared with the prior art, the embodiments of the present application have the following beneficial effects: the film prepared by using ink can maintain conductivity and, due to its good density, can also inhibit the damage of the hole functional layer to the electron functional layer, thereby obtaining better charge generation and separation capabilities, as well as better device performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the scheme of the present application, a brief introduction is given below to the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0048] Figure 1 This is a synthesis process of an embodiment of a conductive polymer containing a cross-linking group in the present application;
[0049] Figure 2 is a flow chart of an embodiment of a method for preparing a charge generation layer in the present application;
[0050] Figure 3 is a schematic structural diagram of an embodiment of a charge generation layer in the present application;
[0051] Figure 4 It is a schematic structural diagram of an embodiment of a light-emitting device in the present application.
[0052] Figure numerals: 10, first electrode; 20, hole injection layer; 30a, first light-emitting unit; 31a, hole transport layer; 32a, light-emitting layer; 33a, electron transport layer; 40, charge generation layer; 41, electron functional layer; 42, blocking layer; 43, hole functional layer; 30b, second light-emitting unit; 31b, hole transport layer; 32b, light-emitting layer; 33b, electron transport layer; 50, electron injection layer; 60, second electrode. DETAILED DESCRIPTION
[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of this application; the terms used in the specification of the application herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned drawings are intended to cover non-exclusive inclusions. The terms "first", "second", etc. in the specification and claims of this application or the above-mentioned drawings are used to distinguish different objects, not to describe a specific order.
[0054] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0055] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the accompanying drawings.
[0056] In the prior art stacked devices, N-type metal oxides (such as zinc oxide) are often used to prepare the electronic functional layer of the charge generation layer. Conductive polymers (such as PEDOT) are often used to prepare the hole functional layer of the charge generation layer. PSS is usually used for doping to improve the dispersibility and conductivity of PEDOT, but the dispersion of PEDOT:PSS is an acidic aqueous solution. Its acidity will etch the N-type metal oxide on the one hand, and cause its own dedoping at the same time. In addition, the introduction of water into the light-emitting device will have an adverse effect on the electrical performance and reliability of the device; another way is to prepare the doped PEDOT into dispersible nanoparticles, but the density of its film is limited; in addition, solubilizing substituents can be introduced into PEDOT to improve its solubility. Better solubility can make the solubilized PEDOT form a dense film, but the film prepared in the device still needs to be resistant to organic solvents to ensure the normal progress of subsequent processes.
[0057] An embodiment of the present application provides an ink, which includes: a conductive polymer containing a cross-linking group, an organic substance containing a thiol group, and a solvent, wherein the thiol group is configured to be capable of cross-linking reaction with the cross-linking group.
[0058] The ink provided in this embodiment can be used to prepare a barrier layer between the electron functional layer and the hole functional layer in the charge generation layer. The thiol group of the ink can cross-link with the cross-linking group, so that the prepared film has good density and has resistance to organic solvents. The film prepared using the ink provided in this embodiment has good density and can inhibit the damage of the hole functional layer to the electron functional layer, thereby obtaining better charge generation and separation capabilities, as well as better device performance.
[0059] Furthermore, the conductive polymer has the following general formula I:
[0060]
[0061] Wherein, m is selected from an integer of 5 to 100;
[0062] R is the crosslinking group, and R contains a vinyl group.
[0063] In some optional implementations of this embodiment, m is selected from any one of 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, etc., or a range between any two of them.
[0064] In this embodiment, the thiol group and the cross-linking group undergo a thiol-ene cross-linking reaction, and the cross-linked film has resistance to organic solvents; and compared with other cross-linking groups, the thiol-ene cross-linking reaction can be carried out at low temperature to avoid high temperature affecting the device performance of the light-emitting unit.
[0065] In this embodiment, the conductive polymer is a poly (3,4-ethylenedioxythiophene) (PEDOT) derivative containing a vinyl crosslinking group; specifically, it is a copolymer formed by polymerization of a substituted 3,4-ethylenedioxythiophene (EDOT, the first thiophene unit in Formula I) and an EDOT dimer (the second and third thiophene units in Formula I).
[0066] Furthermore, the vinyl group is selected from norbornene end groups and has the following general formula II:
[0067]
[0068] Here, x is an integer selected from 0 to 5.
[0069] In some optional implementations of this embodiment, x is selected from any one of 1, 2, 3, 4, 5, etc., or a range between any two of them.
[0070] like Figure 1As shown, further, the synthesis process of the conductive polymer containing a cross-linking group is as follows: 1g of EDOT-OH is dissolved in 25mL of anhydrous tetrahydrofuran, the flask is immersed in an ice bath under N2 to cool the solution, 0.19g of potassium iodide and 0.278g of NaOH suspension are added and stirred for 30 minutes, then 0.76mL of methyl 3-bromopropionate is added dropwise, and stirred for 48h under N2, then deionized water is added to quench the reaction, and tetrahydrofuran is removed under reduced pressure. The water mixture is extracted with ethyl acetate and dried with magnesium sulfate, filtered and concentrated under reduced pressure, and n-hexane: ethyl acetate = 5:1 is used as the column chromatography mobile phase to extract the concentrate to obtain the illustrated compound (1). Add 1g of compound (1) and 0.5g of 5-norbornene-2-ol to a flask, add 0.1g of NaOH, stir at 160°C for 6h, then add CHCl2 to filter out the precipitate, concentrate the filtrate and use n-hexane:ethyl acetate = 5:1 as the column chromatography mobile phase for crude extraction to obtain the illustrated compound (2). Dissolve 0.5g of dimeric EDOT and 0.5g of compound (2) in 10mL of dry chloroform, mix with 10mL of FeCl3 (1.84g) chloroform suspension, and stir at room temperature under N2 for 48h. Pour the mixture into 400mL of methanol to filter out the precipitated copolymer, then dissolve it in chloroform, repeat washing twice and dry.
[0071] It should be noted that the product of this synthesis method will contain the polymerization of compound 2 itself (as an impurity), but the polymerization product of dimeric EDOT itself is an insoluble product and will be removed during purification.
[0072] Furthermore, the mass average molecular weight (Mw) of the conductive polymer is greater than 10,000.
[0073] Furthermore, the organic compound is selected from at least one of formulas I, II, III, IV, V, and VI:
[0074]
[0075]
[0076] wherein n is independently selected from integers ranging from 10 to 100.
[0077] In some optional embodiments of this embodiment, n in formula VI is selected from any integer among 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, etc., or a range between any two integers.
[0078] Specifically, formula I is pentaerythritol tetrakis (3-mercaptopropionate), CAS number: 7575-23-7.
[0079] Specifically, formula II is trimethylolpropane tris(3-mercaptopropionate), and its CAS number is 33007-83-9.
[0080] Specifically, formula III is dithiothreitol, and its CAS number is 3483-12-3.
[0081] Specifically, formula IV is 1,6-hexanedithiol, and its CAS number is: 1191-43-1.
[0082] Specifically, Formula V is PVA functionalized thiol (thiolated polyvinyl alcohol), and the synthesis method is described in Chinese Journal of Applied Chemistry, Volume 34, Issue 3, Pages 291-299.
[0083] Specifically, Formula VI is 4-arm PEG-functionalized thiol (4Arm-PEG-Thiol), selected from Sigma, catalog number JKA7008.
[0084] In this embodiment, the organic matter is a polythiol organic matter, which contains a polythiol group and is easy to undergo a cross-linking reaction with a cross-linking group.
[0085] Furthermore, the mass ratio of the conductive polymer to the organic matter is (1:1) to (50:1).
[0086] In this embodiment, the mass ratio of the conductive polymer to the organic matter is limited to (1:1) to (50:1) to avoid too much or too little organic matter, which would make it difficult to achieve effective cross-linking.
[0087] In some optional implementations of this embodiment, the mass ratio of the conductive polymer to the organic matter is any one of 1:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1, etc., or a range between any two of them.
[0088] Furthermore, the solvent is selected from at least one of tetralin, decalin, cyclohexylbenzene, xylene, toluene, chlorobenzene, chloroform, anisole, methyl benzoate, ethyl benzoate, n-propyl benzoate, cyclohexanone, tetrahydrofuran, dioxane, and acetophenone.
[0089] In this embodiment, the above solvent is a medium-low level solvent. The use of the above polar solvent can avoid damage to the underlying electronic functional layer while taking into account the solubility of the conductive polymer containing cross-linking groups and the organic matter containing thiol groups.
[0090] The above scheme is further described below in conjunction with specific implementation examples. The preferred embodiments of the present invention are described in detail as follows:
[0091] Embodiment 1:
[0092] Synthesis of conductive polymer containing cross-linking groups: 1 g of EDOT-OH was dissolved in 25 mL of anhydrous tetrahydrofuran, and the flask was immersed in an ice bath under N2 to cool the solution, 0.19 g of potassium iodide and 0.278 g of NaOH suspension were added and stirred for 30 minutes, and then 0.76 mL of methyl 3-bromopropionate was added dropwise, and stirred for 48 h under N2, and then deionized water was added to quench the reaction, and tetrahydrofuran was removed under reduced pressure. The water mixture was extracted with ethyl acetate and dried with magnesium sulfate, filtered and concentrated under reduced pressure, and n-hexane: ethyl acetate = 5:1 was used as the column chromatography mobile phase to extract the concentrate to obtain compound 1. Add 1g of compound 1 and 0.5g of 5-norbornene-2-ol to a flask, and add 0.1g of NaOH, stir at 160°C for 6h, then add CHCl2 to filter out the precipitate, concentrate the filtrate and use n-hexane: ethyl acetate = 5:1 as the column chromatography mobile phase to crudely extract the concentrate to obtain compound 2, the molecular ion peak (M / Z) of compound 2: 334.12 (M+). Dissolve 0.5g of dimerized EDOT and 0.5g of compound 2 in 10mL of dry chloroform, and mix with 10mL of FeCl3 (1.84g) chloroform suspension, and stir at room temperature under N2 for 48h. Pour the mixture into 400mL of methanol to filter out the precipitated copolymer, then dissolve it in chloroform, wash it twice and dry it; finally obtain the following Figure 1 The conductive polymer shown has a weight average molecular weight (Mw) of 11,500 and a polymer dispersibility index (DPI, characterizing molecular weight distribution) of 5.2.
[0093] Ink preparation: The above-synthesized conductive polymer containing cross-linking groups and organic matter containing thiol groups are mixed: (Pentaerythritol tetrakis(3-mercaptopropionate)) was dissolved in chlorobenzene as ink.
[0094] Thin film preparation: The ITO anode substrate was cleaned and then treated under UV conditions for 15 minutes to increase its work function and wettability; then a 30nm thick ink was spin-coated on the treated ITO substrate, with a mass ratio of a conductive polymer containing a cross-linking group to an organic matter containing a thiol group of 10:1, and baked at 150°C for 10 minutes to obtain a thin film.
[0095] Embodiment 2:
[0096] The difference from Example 1 is that the mass ratio of the conductive polymer containing a cross-linking group to the organic matter containing a thiol group is 1:1.
[0097] Embodiment 3:
[0098] The difference from Example 1 is that the mass ratio of the conductive polymer containing a cross-linking group to the organic matter containing a thiol group is 50:1.
[0099] Embodiment 4:
[0100] The difference from Example 1 is that the mass ratio of the conductive polymer containing a cross-linking group to the organic matter containing a thiol group is 1:2.
[0101] Embodiment 5:
[0102] The difference from Example 1 is that the mass ratio of the conductive polymer containing a cross-linking group to the organic matter containing a thiol group is 100:1.
[0103] Embodiment 6:
[0104] The difference from Example 1 is that the organic compound containing a thiol group is selected from:
[0105]
[0106] Embodiment 7:
[0107] The difference from Example 1 is that the organic compound containing a thiol group is selected from:
[0108]
[0109] Embodiment 8:
[0110] The difference from Example 1 is that the organic compound containing a thiol group is selected from:
[0111]
[0112] Embodiment 9:
[0113] The difference from Example 1 is that the organic compound containing a thiol group is selected from:
[0114]
[0115] Embodiment 10:
[0116] The difference from Example 1 is that the organic compound containing a thiol group is selected from:
[0117]
[0118] Embodiment 11:
[0119] The difference from Example 1 is that when synthesizing a conductive polymer containing a cross-linking group, the reactant 3-bromopropionic acid methyl ester is replaced by 4-bromobutyric acid methyl ester; the molecular ion peak (M / Z) of compound 2 is 348.14 (M+); the weight average molecular weight (Mw) of the conductive polymer is 10470, and the polymer dispersity index (DPI, characterizing the molecular weight distribution) is 5.5.
[0120] Comparative Example 1:
[0121] The difference from Example 1 is that a conductive polymer containing cross-linking groups is spin-coated on the treated ITO substrate, the mass ratio of the conductive polymer containing cross-linking groups to the organic matter containing thiol groups is 1:0, and the film is baked at 150° C. for 10 minutes to obtain a thin film.
[0122] Experimental test analysis: The anti-solvent ability test was carried out on the films prepared in Examples 1 to 11 and Comparative Example 1: Chlorobenzene was used to clean the films, and the analysis results are shown in Table 1.
[0123] Table 1
[0124]
[0125]
[0126] It can be seen from Example 1 and Comparative Example 1 in Table 1 that, under the cleaning of the organic solvent chlorobenzene, the film thickness of Comparative Example 1 becomes significantly thinner, while the film thickness of Example 1 does not change significantly, indicating that when a conductive polymer containing a cross-linking group is disposed on the substrate, since the cross-linking group does not cross-link with the thiol group, the prepared film has poor density and does not have resistance to organic solvents.
[0127] It can be seen from Examples 1 to 5 that when the mass ratio of the conductive polymer containing cross-linking groups to the organic matter containing thiol groups is 10:1, the film has good anti-dissolution ability; although when the proportion of the organic matter containing thiol groups is increased or decreased alone, the thickness of the film varies greatly due to incomplete cross-linking, but the anti-dissolution ability of Examples 2 to 5 is still better than that of Comparative Example 1.
[0128] It can be seen from Example 1 and Example 6 to Example 10 in Table 1 that after the material selected for the organic matter containing a thiol group is replaced, the film still maintains good anti-solvent ability; it can be seen from Example 1 and Example 11 in Table 1 that when the conductive polymer containing a cross-linking group is synthesized, after the reactants are replaced, the film still maintains good anti-solvent ability.
[0129] In summary, the thiol groups of the ink can react with the cross-linking groups to cross-link, so that the prepared film has good density and resistance to organic solvents; therefore, the film prepared using the ink provided in this embodiment has good density and can inhibit the damage of the hole functional layer to the electron functional layer, thereby obtaining better charge generation and separation capabilities, as well as better device performance.
[0130] The present application also provides a method for preparing a thin film, such as Figure 2 As shown, the preparation method comprises the following steps:
[0131] S10, providing a preform, and placing ink on the preform to obtain a liquid film; the ink comprises a conductive polymer containing a cross-linking group, an organic substance containing a thiol group, and a solvent;
[0132] S20, placing the liquid film at a first temperature to react to obtain a thin film.
[0133] The method for preparing the film provided in this embodiment can be used to prepare a barrier layer between the electron functional layer and the hole functional layer in the charge generation layer. The conductive polymer of the ink makes the prepared film conductive, and the thiol group of the ink can cross-link with the cross-linking group, so that the prepared film has good density and resistance to organic solvents. The film prepared by using the ink provided in this embodiment can not only maintain conductivity, but also inhibit the damage of the hole functional layer to the electron functional layer due to its good density, thereby obtaining better charge generation and separation capabilities, as well as better device performance.
[0134] Furthermore, the first temperature is 120-200°C.
[0135] In this embodiment, the first temperature needs to be higher than the temperature at which the cross-linking groups and the thiol groups are cross-linked. The cross-linking temperature varies depending on the material, and this application does not limit the cross-linking temperature.
[0136] In some optional implementations of this embodiment, the first temperature is any one of 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc., or a range between any two of them.
[0137] Furthermore, the processing of the liquid film at the first temperature specifically includes baking the liquid film at the first temperature.
[0138] In this embodiment, the conductive polymer containing cross-linking groups and the organic group containing thiol groups in the liquid film undergo a thiol-ene cross-linking reaction during baking, and the cross-linked film has an ability to resist organic solvents.
[0139] Further, refer to Figure 4The preform includes a first electrode 10, a first light-emitting unit 30a and an electronic functional layer 41 which are stacked in sequence.
[0140] The present application also provides a charge generation layer 40, such as Figure 3 As shown, the charge generating layer 40 includes a barrier layer 42, and the barrier layer 42 is prepared by using the ink as described above, or the barrier layer 42 is prepared by using the preparation method as described above.
[0141] The ink used in the barrier layer 42 of the charge generation layer 40 provided in this embodiment includes a conductive polymer containing a cross-linking group, an organic substance containing a thiol group, and a solvent. The thiol group of the ink can react with the cross-linking group to make the prepared barrier layer 42 have good compactness and resistance to organic solvents. The barrier layer 42 prepared by the ink provided in this embodiment can also inhibit the film located on the upper layer of the barrier layer 42 (i.e., the hole functional layer 43 described below) from damaging the film located on the lower layer of the barrier layer 42 (i.e., the electronic functional layer 41 described below) due to its good compactness, thereby obtaining better charge generation and separation capabilities, as well as better device performance.
[0142] Furthermore, the charge generation layer 40 includes a hole function layer 43 and an electron function layer 41 which are stacked, the barrier layer 42 is disposed between the hole function layer 43 and the electron function layer 41, and the material of the hole function layer 43 includes a hole injection material and an oxidant.
[0143] In this embodiment, the hole functional layer 43 is used to achieve hole injection.
[0144] In this embodiment, the electronic functional layer 41 is used to achieve electron injection.
[0145] In this embodiment, the oxidant can oxidize the barrier layer 42 to enhance the conductivity of the barrier layer 42 .
[0146] In this embodiment, a conductive polymer containing a cross-linking group and an organic ink containing a thiol group are used to prepare a barrier layer 42 with good density, and the barrier layer 42 is doped by utilizing the oxidizing property of the hole functional layer 43 material, thereby further enhancing the conductivity of the barrier layer 42. It should be pointed out that the conductivity of the barrier layer 42 will directly affect the performance of the charge generation layer, and an efficient charge generation layer cannot be constructed without doping the barrier layer 42.
[0147] Furthermore, the mass ratio of the hole injection material to the oxidant is (1:0) to (1:1).
[0148] In this embodiment, the mass ratio of the hole injection material and the oxidant is limited to (1:0) to (1:1) to avoid too much or too little hole injection material, which may make it difficult to achieve effective oxidation or hole injection.
[0149] In some optional implementations of this embodiment, the mass ratio of the hole injection material to the oxidant is any one of 1:0, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, etc., or a range between any two of them.
[0150] Furthermore, the hole injection material is selected from at least one of phosphomolybdic acid, phosphotungstic acid, ammonium molybdate, metavanadic acid, metatungstic acid, vanadium acetonate, ethoxide tungsten, ethoxide molybdenum, PEDOT:PSS (AI 4083), HATCN, CN6-CP, NDP-9, F4TCNQ and F6TCNQ.
[0151] In this embodiment, the hole functional layer 43 is prepared by using the hole injection material mentioned above, which can not only realize hole injection, but also enhance the conductivity of the barrier layer 42 due to its oxidizability.
[0152] Furthermore, the oxidant includes at least one of iron (III) chloride, antimony chloride, iron benzenesulfonate (FeTos3), iron pentafluorobenzenesulfonate (FeTos3), iron (III) trifluoromethanesulfonate, nitrosyl hexafluorophosphate, tris (pentafluorophenyl) boric acid, and tris (4-bromophenyl) ammonium hexachloroantimonate (Magic blue).
[0153] In this embodiment, the oxidant is a Lewis acid, which has a high oxidizing property and is beneficial for oxidizing the barrier layer 42 to improve the conductivity of the barrier layer 42 .
[0154] Furthermore, the material of the electronic functional layer 41 includes metal oxide.
[0155] Furthermore, the metal oxide is selected from at least one of doped or undoped zinc oxide, tin oxide, titanium oxide, and zirconium oxide, and the doped elements include at least one of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium.
[0156] Furthermore, the material of the electronic functional layer 41 also includes an organic material, and the organic material is selected from at least one of aliphatic amine polymers and organic electron transport materials.
[0157] In this embodiment, the organic material is used to assist electron injection.
[0158] Furthermore, the fatty amine polymer is selected from at least one of polyethyleneimine and polyethoxyethyleneimine.
[0159] Furthermore, the mass ratio of the metal oxide to the organic material is (1:0.05) to (1:1).
[0160] In this embodiment, when the charge generation layer 40 is used as a charge generation layer, the metal oxide and the hole functional layer 43 are required to have a shorter spatial distance, and the mass ratio of the metal oxide to the organic material is limited to (1:0.05) to (1:1), which can prevent excessive organic materials from affecting the distribution density of the metal oxide and further affecting the performance of the charge generation layer.
[0161] In some optional implementations of this embodiment, the mass ratio of the metal oxide to the organic material is any one of 1:0.05, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, etc., or a range between any two of them.
[0162] Furthermore, the barrier layer 42 has a thickness of 5 to 100 nm.
[0163] In this embodiment, the thickness of the barrier layer 42 is limited to 5-100 nm, so as to avoid the difficulty in preparation and performance control due to the barrier layer 42 being too thin, and also to avoid the influence on light transmittance due to the barrier layer 42 being too thick.
[0164] In some optional implementations of this embodiment, the thickness of the barrier layer 42 is any one of 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc., or a range between any two of them.
[0165] Furthermore, the thickness of the hole function layer 43 is 5-100 nm.
[0166] In this embodiment, the thickness of the hole functional layer 43 is limited to 5-100 nm to avoid the difficulty in preparation and performance control due to the hole functional layer 43 being too thin, and to avoid the influence of transmittance due to the hole functional layer 43 being too thick.
[0167] In some optional implementations of this embodiment, the thickness of the hole functional layer 43 is any one of 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, etc., or a range between any two of them.
[0168] Furthermore, the thickness of the electronic functional layer 41 is 5-100 nm.
[0169] In this embodiment, the thickness of the electronic functional layer 41 is limited to 5-100 nm to avoid the difficulty in preparation and performance control due to the electronic functional layer 41 being too thin, and also to avoid the influence of light transmittance due to the electronic functional layer 41 being too thick.
[0170] In some optional implementations of this embodiment, the thickness of the electronic functional layer 41 is any one of 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, etc., or a range between any two of them.
[0171] The present application also provides a light emitting device, such as Figure 4 As shown, the light emitting device includes a first electrode 10, a first light emitting unit 30a, the charge generation layer 40 as described above, a second light emitting unit 30b and a second electrode 60 which are stacked.
[0172] The ink used in the barrier layer 42 of the charge generation layer 40 provided in this embodiment includes a conductive polymer containing a cross-linking group, an organic substance containing a thiol group, and a solvent. The thiol group of the ink can react with the cross-linking group to make the prepared barrier layer 42 have good compactness and resistance to organic solvents. The barrier layer 42 prepared by the ink provided in this embodiment can also inhibit the destruction of the film (i.e., the electron functional layer 41) located below the barrier layer 42 by the film (i.e., the hole functional layer 43) on the upper layer of the barrier layer 42, due to its good compactness, thereby obtaining better charge generation and separation capabilities, as well as better device performance.
[0173] In this embodiment, the first electrode 10 is an anode; the second electrode 60 is a cathode.
[0174] In this embodiment, the light-emitting device may further include a third light-emitting unit (not shown), and the charge generating device 40 is provided between the third light-emitting unit and the second light-emitting unit 30b; the light-emitting device may further include a fourth light-emitting unit (not shown), and the charge generating device 40 is provided between the fourth light-emitting unit and the third light-emitting unit; and so on, the light-emitting device may further include a fifth light-emitting unit, and so on, and the present application does not limit this.
[0175] Furthermore, each of the first electrode 10 and the second electrode 60 is selected from one or more of a metal electrode, a silicon-carbon electrode, a doped or undoped metal oxide electrode and a composite electrode; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca and Mg; the material of the silicon-carbon electrode is selected from at least one of silicon, graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, At least one of GZO, IZO, MZO and AMO; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2.
[0176] Further, the first light-emitting unit 30a includes a hole transport layer 31a, a light-emitting layer 32a and an electron transport layer 33a which are stacked in sequence, the hole transport layer 31a is arranged adjacent to the first electrode 10, and the electron transport layer 33a is arranged adjacent to the second electrode 60; the second light-emitting unit 30b includes a hole transport layer 31b, a light-emitting layer 32b and an electron transport layer 33b which are stacked in sequence, the hole transport layer 31b is arranged adjacent to the first electrode 10, and the electron transport layer 33b is arranged adjacent to the second electrode 60.
[0177] Further, the materials of the hole transport layer 31a and the hole transport layer 31b are independently selected from at least one of TFB (poly [(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine)]), poly-TPD (poly [N, N'-bis(4-butylphenyl)-N, N'-bis(phenyl)-benzidine]), PVK (polyvinylcarbazole), BFB (poly [(9,9-dioctylfluorenyl-2,7-diyl)-another-(N, N'-bis{4-butylphenyl}-benzidine-N, N'-{1,4-diphenyl})]), and PFHB (poly [(9,9-dihexylfluorenyl-2,7-diyl)-another-(N, N'-bis-{p-butylphenyl}-1,4-diaminophenyl)]).
[0178] Furthermore, the light-emitting layer 32a and the light-emitting layer 32b are both quantum dot light-emitting layers or organic light-emitting layers; the material of the quantum dot light-emitting layer includes at least one of a single structure quantum dot and a core-shell structure quantum dot, and the material of the single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound, wherein the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, At least one of HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, At least one of SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, G At least one of aInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs or InAlPSb, the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; the core of the quantum dots of the core-shell structure includes any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure includes CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS, ZnS and at least one of the above-mentioned single-structure quantum dots;The material of the organic light-emitting layer includes at least one of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine-C2,N)iridium(III), 4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine-C2,N)iridium, diarylanthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials and DBP fluorescent materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives.;
[0179] Further, the materials of the electron transport layer 33a and the electron transport layer 33b are independently selected from at least one of doped or undoped metal oxides and organic electron transport materials; the doped or undoped metal oxide is selected from at least one of doped or undoped zinc oxide, tin oxide, titanium oxide, and zirconium oxide, and the doped elements include at least one of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic electron transport material is selected from [6,6]-phenyl C71 butyric acid methyl ester, [6, 6]-phenyl C61 butyric acid methyl ester, organic fullerene materials, 2-ethyl-1-(4-(10-(2-naphthyl)-9-anthryl)phenyl)-1H-benzimidazole, 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), 3,3'-[5'-[3-(3-pyridyl)phenyl](TmPyPb), 4,6-bis(3,5-di(3-pyridyl)phenyl)-2-methylpyrimidine (B3PYMPM), phenylpyridinium beryllium (Bepp2) 、1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), 3-(biphenyl-4-yl)-5-(4-tert-butylphenyl)-4-phenyl-4H-1,2,4-triazole (TAZ), 1,3,5-tris[(3-pyridyl)-3-phenyl]benzene (TmPyPb), tris-(8-hydroxyquinoline)aluminum (Alq3), 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline (BCP), 4,7-diphenyl-1,10-phenanthroline (Bphen), poly [(9,9-bis (3'- ((N, N-dimethyl) -N-ethylammonium) -propyl) -2,7-fluorene) -2,7- (9,9-dioctylfluorene)] dibromide (PFN-Br), poly [(9,9-bis (3'- (N, N-dimethylamino) propyl) -2,7-fluorene) -2,7- (9,9-dioctylfluorene)] (PFN-DOF), 2,7-bis (diphenylphosphinyl) -9,9'-spirobi [fluorene] (SPPO13) at least one.
[0180] Furthermore, the light emitting device further includes a hole injection layer 20 , and the hole injection layer 20 is disposed between the first light emitting unit 30 a and the first electrode 10 .
[0181] The material of the hole injection layer 20 is selected from at least one of phosphomolybdic acid, phosphotungstic acid, ammonium molybdate, metavanadic acid, metatungstic acid, vanadium acetonate acetate, tungsten ethoxide, molybdenum ethoxide, PEDOT:PSS (AI 4083), HATCN, CN6-CP, NDP-9, F4TCNQ and F6TCNQ.
[0182] Furthermore, the light emitting device further includes an electron injection layer 50 , and the electron injection layer 50 is disposed between the second light emitting unit 30 b and the second electrode 60 .
[0183] The material of the electron injection layer 50 is selected from at least one of doped or undoped metal oxides and organic electron transport materials; the doped or undoped metal oxide is selected from at least one of doped or undoped zinc oxide, tin oxide, titanium oxide, and zirconium oxide, and the doped element includes at least one of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic electron transport material is selected from [6,6]-phenyl C71 butyric acid methyl ester, [6,6]-phenyl C61 butyric acid methyl ester, organic Fullerene materials, 2-ethyl-1-(4-(10-(2-naphthyl)-9-anthryl)phenyl)-1H-benzimidazole, 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), 3,3'-[5'-[3-(3-pyridyl)phenyl](TmPyPb), 4,6-bis(3,5-di(3-pyridyl)phenyl)-2-methylpyrimidine (B3PYMPM), phenylpyridinium beryllium (Bepp2), 1,3,5-tri(1 -phenyl-1H-benzimidazol-2-yl)benzene (TPBi), 3-(biphenyl-4-yl)-5-(4-tert-butylphenyl)-4-phenyl-4H-1,2,4-triazole (TAZ), 1,3,5-tris[(3-pyridyl)-3-phenyl]benzene (TmPyPb), tris-(8-hydroxyquinoline)aluminum (Alq3), 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline (BCP), 4,7-diphenyl-1,10-phenanthroline (Bphe n), poly [(9,9-bis (3'- ((N, N-dimethyl) -N-ethylammonium) -propyl) -2,7-fluorene) -2,7- (9,9-dioctylfluorene)] dibromide (PFN-Br), poly [(9,9-bis (3'- (N, N-dimethylamino) propyl) -2,7-fluorene) -2,7- (9,9-dioctylfluorene)] (PFN-DOF), 2,7-bis (diphenylphosphinyl) -9,9'-spirobis [fluorene] (SPPO13) at least one.
[0184] Furthermore, the thickness of the first electrode 10 is 10-200 nm.
[0185] In some optional implementations of this embodiment, the thickness of the first electrode 10 is any one of 10 nm, 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, etc., or a range between any two of them.
[0186] Furthermore, the hole injection layer 20 has a thickness of 10-100 nm.
[0187] In some optional implementations of this embodiment, the thickness of the hole injection layer 20 is any one of 10 nm, 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, etc., or in a range between any two of them.
[0188] Furthermore, the hole transport layer 31a has a thickness of 10-100 nm.
[0189] In some optional implementations of this embodiment, the thickness of the hole transport layer 31a is any one of 10 nm, 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, etc., or in the range between any two of them.
[0190] Furthermore, the thickness of the light emitting layer 32a is 20-100 nm.
[0191] In some optional implementations of this embodiment, the thickness of the light-emitting layer 32a is any one of 20nm, 40nm, 60nm, 80nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, etc., or a range between any two of them.
[0192] Furthermore, the thickness of the electron transport layer 33a is 10-50 nm.
[0193] In some optional implementations of this embodiment, the thickness of the electron transport layer 33a is any one of 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, etc., or in a range between any two of them.
[0194] Furthermore, the hole transport layer 31b has a thickness of 10-100 nm.
[0195] In some optional implementations of this embodiment, the thickness of the hole transport layer 31b is any one of 10 nm, 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, etc., or in the range between any two of them.
[0196] Furthermore, the thickness of the light emitting layer 32b is 20-100 nm.
[0197] In some optional implementations of this embodiment, the thickness of the light-emitting layer 32b is any one of 20nm, 40nm, 60nm, 80nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, etc., or a range between any two of them.
[0198] Furthermore, the thickness of the electron transport layer 33b is 10-50 nm.
[0199] In some optional implementations of this embodiment, the thickness of the electron transport layer 33b is any one of 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, etc., or in a range between any two of them.
[0200] Furthermore, the thickness of the electron injection layer 50 is 0-5 nm.
[0201] In some optional implementations of this embodiment, the thickness of the electron injection layer 50 is any one of 0 nm, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, etc., or a range between any two of them.
[0202] Furthermore, the thickness of the second electrode 60 is 10-100 nm.
[0203] In some optional implementations of this embodiment, the thickness of the second electrode 60 is any one of 10nm, 20nm, 40nm, 60nm, 80nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, etc., or a range between any two of them.
[0204] An embodiment of the present application further provides a display device, wherein the display device includes the charge generating layer as described above, or includes the light-emitting device as described above.
[0205] The ink used for the barrier layer 42 in the charge generation layer 40 provided in this embodiment includes a conductive polymer containing a cross-linking group, an organic substance containing a thiol group, and a solvent. The thiol group of the ink can react with the cross-linking group to make the prepared barrier layer 42 have good compactness and resistance to organic solvents. The barrier layer 42 prepared by using the ink provided in this embodiment can also suppress the hole functional layer 43 on the upper layer of the barrier layer 42 from damaging the electronic functional layer 41 located under the barrier layer 42 due to its good compactness, thereby obtaining better charge generation and separation capabilities, as well as better device performance.
[0206] The above scheme is further described below in conjunction with specific implementation examples. The preferred embodiments of the present invention are described in detail as follows:
[0207] Embodiment 12:
[0208] Synthesis of conductive polymer containing cross-linking groups: 1 g of EDOT-OH was dissolved in 25 mL of anhydrous tetrahydrofuran, and the flask was immersed in an ice bath under N2 to cool the solution, 0.19 g of potassium iodide and 0.278 g of NaOH suspension were added and stirred for 30 minutes, and then 0.76 mL of methyl 3-bromopropionate was added dropwise, and stirred for 48 h under N2, and then deionized water was added to quench the reaction, and tetrahydrofuran was removed under reduced pressure. The water mixture was extracted with ethyl acetate and dried with magnesium sulfate, filtered and concentrated under reduced pressure, and n-hexane: ethyl acetate = 5:1 was used as the column chromatography mobile phase to extract the concentrate to obtain compound 1. Add 1g of compound 1 and 0.5g of 5-norbornene-2-ol to a flask, and add 0.1g of NaOH, stir at 160°C for 6h, then add CHCl2 to filter out the precipitate, concentrate the filtrate and use n-hexane: ethyl acetate = 5:1 as the column chromatography mobile phase to crudely extract the concentrate to obtain compound 2, the molecular ion peak (M / Z) of compound 2: 334.12 (M+). Dissolve 0.5g of dimerized EDOT and 0.5g of compound 2 in 10mL of dry chloroform, and mix with 10mL of FeCl3 (1.84g) chloroform suspension, and stir at room temperature under N2 for 48h. Pour the mixture into 400mL of methanol to filter out the precipitated copolymer, then dissolve it in chloroform, wash it twice and dry it; finally obtain the following Figure 1 The conductive polymer shown has a weight average molecular weight (Mw) of 11,500 and a polymer dispersibility index (DPI, characterizing molecular weight distribution) of 5.2.
[0209] Ink preparation: The above-synthesized conductive polymer containing cross-linking groups and organic matter containing thiol groups are mixed: Dissolved in chlorobenzene as ink.
[0210] Device preparation: The ITO anode substrate (first electrode) was cleaned and then treated under UV conditions for 15 minutes to increase its work function and wettability; then, a 30nm thick PEDOT:PSS was spin-coated on the treated ITO substrate and baked at 150°C in an air atmosphere for 20 minutes to obtain a hole injection layer; then, TFB was spin-coated on the PEDOT:PSS substrate with a thickness of 30nm, and then baked at 180°C in a nitrogen environment for 60 minutes to obtain a hole transport layer of the first light-emitting unit; then, a 60nm thick polymer F8BT was spin-coated on the hole transport layer and baked at 150°C for 10 minutes to obtain an organic light-emitting layer of the first light-emitting unit; then, ZnO (particle size ~8nm) and a 5% mass fraction PEIE composite film were spin-coated as the electronic functional layer of the charge generation layer, with a total thickness of 20nm, and at 1 Anneal at 20℃ for 20min; then spin-coat a 30nm thick ink on it, with the mass ratio of the conductive polymer containing cross-linking groups to the organic matter containing thiol groups being 10:1, and bake at 150℃ for 10min to obtain a barrier layer for the charge generation layer; then spin-coat a 20nm thick layer of phosphomolybdic acid on it, and anneal at 120℃ for 20min to obtain a hole functional layer for charge generation; then spin-coat TFB with a thickness of 30nm, and bake at 180℃ for 60min to obtain the hole transport layer of the second light-emitting unit; then spin-coat a 60nm thick polymer F8BT on the hole transport layer, and bake at 150℃ for 10min to obtain the organic light-emitting layer of the second light-emitting unit; finally vacuum evaporate 1nm of LiF and 100nm thick Al to obtain the second electrode; finally encapsulate and anneal at 80℃ for 30min.
[0211] Embodiment 13:
[0212] The difference from Example 12 is that the mass ratio of the conductive polymer containing a cross-linking group to the organic matter containing a thiol group is 1:1.
[0213] Embodiment 14:
[0214] The difference from Example 12 is that the mass ratio of the conductive polymer containing a cross-linking group to the organic matter containing a thiol group is 50:1.
[0215] Embodiment 15:
[0216] The difference from Example 12 is that the mass ratio of the conductive polymer containing a cross-linking group to the organic matter containing a thiol group is 1:2.
[0217] Embodiment 16:
[0218] The difference from Example 12 is that the mass ratio of the conductive polymer containing a cross-linking group to the organic matter containing a thiol group is 100:1.
[0219] Embodiment 17:
[0220] The difference from Example 1 is that the organic compound containing a thiol group is selected from:
[0221]
[0222] Embodiment 18:
[0223] The difference from Example 12 is that the organic compound containing a thiol group is selected from:
[0224]
[0225] Embodiment 19:
[0226] The difference from Example 12 is that the organic compound containing a thiol group is selected from:
[0227]
[0228] Embodiment 20:
[0229] The difference from Example 12 is that the organic compound containing a thiol group is selected from:
[0230]
[0231] Embodiment 21:
[0232] The difference from Example 12 is that the organic compound containing a thiol group is selected from:
[0233]
[0234] Embodiment 22:
[0235] The difference from Example 12 is that when synthesizing a conductive polymer containing a cross-linking group, the reactant 3-bromopropionic acid methyl ester is replaced by 4-bromobutyric acid methyl ester; the molecular ion peak (M / Z) of compound 2 is 348.14 (M+); the weight average molecular weight (Mw) of the conductive polymer is 10470, and the polymer dispersity index (DPI, characterizing the molecular weight distribution) is 5.5.
[0236] Comparative Example 2:
[0237] The difference from Example 12 is that there is no barrier layer.
[0238] Embodiment 23:
[0239] The difference from Example 1 is that a 30 nm thick green light QDs ink is spin-coated on the hole transport layer and baked at 100°C for 10 min to obtain the quantum dot light-emitting layer of the lower light-emitting unit; a 20 nm thick green light QDs ink is spin-coated on the hole transport layer and baked at 100°C for 15 min to obtain the quantum dot light-emitting layer of the upper light-emitting unit.
[0240] Comparative Example 3:
[0241] The difference from Example 23 is that there is no barrier layer.
[0242] Experimental test and analysis of light-emitting devices: Experimental test and analysis were performed on the light-emitting devices prepared in Examples 12 to 23 and Comparative Examples 2 to 3. The analysis results are shown in Table 2.
[0243] Table 2
[0244]
[0245] The voltage at a current density of 10 mA / cm2 (J10) was used as the driving voltage index, the current efficiency at a brightness of 1000 nit was used as the efficiency index, and the time it took for the brightness to decay to 95% from an initial brightness of 1000 nit under constant current conditions was used as the life evaluation index.
[0246] It can be seen from Example 12 and Comparative Example 2 and Example 23 and Comparative Example 3 in Table 2 that when there is no barrier layer, the device driving voltage is significantly increased, which indicates that the cross-linking reaction between the thiol group of the organic matter and the cross-linking group of the conductive polymer can make the prepared barrier layer have good density and resistance to organic solvents of the hole functional layer, and can inhibit the damage of the hole functional layer to the electron functional layer, thereby obtaining better charge generation and separation capabilities, as well as better device performance.
[0247] It can be seen from Example 12 and Example 17 to Example 21 in Table 2 that after the material selected for the organic matter containing a thiol group is replaced, the device can still maintain good device performance. It can be seen from Example 12 and Example 22 in Table 2 that when the conductive polymer containing a cross-linking group is synthesized, after the reactant is replaced, the device can still maintain good device performance.
[0248] In addition, it can be seen from Examples 12 to 16 in Table 2 that the device driving voltage is lowest when the mass ratio of the conductive polymer containing cross-linking groups to the organic matter containing thiol groups is 10:1, which indicates that the barrier layer in Example 12 has a good cross-linking effect, and the composite film used as a charge generating unit can efficiently generate and inject charges; further, it indicates that when the proportion of the organic matter containing thiol groups is increased or decreased simply, due to incomplete cross-linking, the barrier layer is destroyed by the solvent of the hole functional layer, resulting in a lower efficiency of the charge generating unit and a significant increase in the driving voltage.
[0249] Obviously, the embodiments described above are only some embodiments of the present application, rather than all embodiments. The preferred embodiments of the present application are given in the accompanying drawings, but they do not limit the patent scope of the present application. The present application can be implemented in many different forms. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive. Although the present application is described in detail with reference to the aforementioned embodiments, for those skilled in the art, it is still possible to modify the technical solutions recorded in the aforementioned specific implementation methods, or to perform equivalent replacement of some of the technical features therein. Any equivalent structure made using the contents of the specification and drawings of this application, directly or indirectly used in other related technical fields, is similarly within the scope of patent protection of this application.
Claims
1. An ink, characterized in that: include: A conductive polymer containing a crosslinking group, an organic substance containing a thiol group, and a solvent, wherein the thiol group is configured to be capable of crosslinking reaction with the crosslinking group.
2. The ink according to claim 1, characterized in that The conductive polymer has the following general formula I: Wherein, m is selected from an integer of 5 to 100; R is the crosslinking group, and R contains a vinyl group.
3. The ink according to claim 2, characterized in that The vinyl group is selected from norbornene end groups and has the following general formula II: Here, x is an integer selected from 0 to 5.
4. The ink according to any one of claims 1 to 3, characterized in that: The mass average molecular weight (Mw) of the conductive polymer is > 10000; and / or The organic compound is selected from at least one of formulas Ⅰ, Ⅱ, Ⅲ, Ⅳ, Ⅴ, and Ⅵ: Wherein, n is selected from an integer of 10 to 100; and / or The mass ratio of the conductive polymer to the organic matter is (1:1) to (50:1).
5. The ink according to claim 1, characterized in that The solvent is selected from at least one of tetralin, decalin, cyclohexylbenzene, xylene, toluene, chlorobenzene, chloroform, anisole, methyl benzoate, ethyl benzoate, n-propyl benzoate, cyclohexanone, tetrahydrofuran, dioxane, and acetophenone.
6. A method for preparing a thin film, characterized in that: The following steps are involved: Providing a preform, and placing ink on the preform to obtain a liquid film; the ink comprises a conductive polymer containing a cross-linking group, an organic substance containing a thiol group, and a solvent; The liquid film is placed at a first temperature to react to obtain a thin film.
7. A charge generating layer, characterized in that: It comprises a barrier layer, wherein the barrier layer is prepared by using the ink according to any one of claims 1 to 5, or the barrier layer is prepared by using the preparation method according to claim 6.
8. The charge generation layer according to claim 7, characterized in that The charge generation layer includes a hole function layer and an electron function layer which are stacked, the barrier layer is arranged between the hole function layer and the electron function layer, and the material of the hole function layer includes a hole injection material and an oxidant.
9. The charge generation layer according to claim 8, characterized in that The thickness of the barrier layer is 5 to 100 nm; and / or The thickness of the hole functional layer is 5 to 100 nm; and / or The mass ratio of the hole injection material to the oxidant is (1:0) to (1:1); and / or The hole injection material is selected from at least one of phosphomolybdic acid, phosphotungstic acid, ammonium molybdate, metavanadic acid, metatungstic acid, vanadyl acetate acetonate, tungsten ethoxide, molybdenum ethoxide, PEDOT:PSS, HATCN, CN6-CP, NDP-9, F4TCNQ and F6TCNQ; and / or The oxidant includes at least one of iron (III) chloride, antimony chloride, iron benzenesulfonate, iron pentafluorobenzenesulfonate (FeTos3), iron (III) trifluoromethanesulfonate, nitrosyl hexafluorophosphate, tris (pentafluorophenyl) boric acid, and tris (4-bromophenyl) ammonium hexachloroantimonate.
10. The charge generation layer according to claim 8, characterized in that The material of the electronic functional layer includes metal oxide; The metal oxide is selected from at least one of doped or undoped zinc oxide, tin oxide, titanium oxide and zirconium oxide, and the doped elements include at least one of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium and gadolinium.
11. The charge generation layer according to claim 10, characterized in that The material of the electronic functional layer further comprises an organic material, wherein the organic material is selected from at least one of aliphatic amine polymers and organic electron transport materials; and / or The thickness of the electronic functional layer is 5-100 nm.
12. A light emitting device, characterized in that: The invention comprises a first electrode, a first light-emitting unit, the charge generation layer according to any one of claims 7 to 10, a second light-emitting unit and a second electrode which are stacked.
13. The light emitting device according to claim 12, characterized in that: The first electrode and the second electrode are each selected from one or more of a metal electrode, a silicon-carbon electrode, a doped or undoped metal oxide electrode and a composite electrode; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca and Mg; the material of the silicon-carbon electrode is selected from at least one of silicon, graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from at least one of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or The first light-emitting unit and the second light-emitting unit each include a hole transport layer, a light-emitting layer and an electron transport layer which are stacked in sequence, the hole transport layer is arranged adjacent to the first electrode, and the electron transport layer is arranged adjacent to the second electrode; the material of the hole transport layer is selected from at least one of TFB, poly-TPD, PVK, BFB, and PFHB; and / or The light-emitting layer is a quantum dot light-emitting layer or an organic light-emitting layer; the material of the quantum dot light-emitting layer includes at least one of a single structure quantum dot and a core-shell structure quantum dot, and the material of the single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound, wherein the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe , at least one of CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, S At least one of nPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInN P, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs or InAlPSb, the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; the core of the quantum dots of the core-shell structure includes any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure includes CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS, ZnS and at least one of the above-mentioned single-structure quantum dots;The material of the organic light-emitting layer includes at least one of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine-C2,N)iridium(III), 4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine-C2,N)iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials and DBP fluorescent materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives; and / or; The material of the electron transport layer is selected from at least one of doped or undoped metal oxides and organic electron transport materials; the doped or undoped metal oxide is selected from at least one of doped or undoped zinc oxide, tin oxide, titanium oxide, and zirconium oxide, and the doped element includes at least one of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic electron transport material is selected from [6,6]-phenyl C71 butyric acid methyl ester, [6,6]-phenyl C61 butyric acid methyl ester, organic fullerene materials, 2-ethyl-1-(4-(10-(2-naphthyl)-9-anthracenyl)phenyl)-1H-benzimidazole, 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene, 3,3'-[5'-[3-(3-pyridyl)phenyl], 4,6-bis(3,5-di(3-pyridyl)phenyl)-2-methylpyrimidine, beryllium phenylidene pyridine, 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene, 3-(biphenyl-4-yl)-5-(4-tert-butylphenyl)-4-phenyl-4H-1,2,4-triazole, 1,3,5-tris[(3-pyridyl)-3-phenyl]benzene, tris-(8-hydroxyquinoline)aluminum, 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline, 4,7-diphenyl-1,10 -phenanthroline, poly[(9,9-bis(3'-((N,N-dimethyl)-N-ethylammonium)-propyl)-2,7-fluorene)-2,7-(9,9-dioctylfluorene)] dibromide, poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)-2,7-fluorene)-2,7-(9,9-dioctylfluorene)], and at least one of 2,7-bis(diphenylphosphinyl)-9,9'-spirobi[fluorene].
14. A display device, characterized in that: A light emitting device comprising the charge generating layer according to any one of claims 7 to 11, or a light emitting device according to claim 12 or 13.
Citation Information
Cited By
Organic light-emitting device
CN122438463A
An organic electroluminescent device
CN122438463B